2016
DOI: 10.1017/s0144686x15001555
|View full text |Cite
|
Sign up to set email alerts
|

Older male and female drivers in car-dependent settings: how much do they use other modes, and do they compensate for reduced driving to maintain mobility?

Abstract: Among the societal and health challenges of population ageing is the continued transport mobility of older people who retain their driving licence, especially in highly car-dependent societies. While issues surrounding loss of a driving licence have been researched, less attention has been paid to variations in physical travel by mode among the growing proportion of older people who retain their driving licence. It is unclear how much they reduce their driving with age, the degree to which they replace driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Hence, it is of paramount importance to conduct a comprehensive study on their daily travel patterns and spatio-temporal travel characteristics. In an effort to understand and improve elderly mobility, numerous studies have focused on the travel patterns of the elderly in Western countries, particularly the United States and Europe (Hildebrand, 2003;Buehler and Nobis, 2010;Currie and Delbosc, 2010;Ipingbemi, 2010;King and Scott-Parker, 2016;Rahman et al, 2016;van den Berg et al, 2016). In most of the countries concerned, driving is the primary means of transport, and only a small proportion of elderly people use public transport services.…”
Section: Ageing Population In Hong Kongmentioning
confidence: 99%
“…Hence, it is of paramount importance to conduct a comprehensive study on their daily travel patterns and spatio-temporal travel characteristics. In an effort to understand and improve elderly mobility, numerous studies have focused on the travel patterns of the elderly in Western countries, particularly the United States and Europe (Hildebrand, 2003;Buehler and Nobis, 2010;Currie and Delbosc, 2010;Ipingbemi, 2010;King and Scott-Parker, 2016;Rahman et al, 2016;van den Berg et al, 2016). In most of the countries concerned, driving is the primary means of transport, and only a small proportion of elderly people use public transport services.…”
Section: Ageing Population In Hong Kongmentioning
confidence: 99%
“…Concerning the socio-demographic variables, it is found that the household structure is not a significant variable, which is in disagreement with previous research activities concerning the relationship between transportation fuel consumption and household variables, as observed in ref. (Büchs and Schnepf, 2013;Clayton et al, 2014;Edwards et al, 2016;King and Scott-Parker, 2016). In this sense, it is worth mentioning that some of the previous literature supported that elderly people tend to use private transportation rather than the public one, which was not observed here (Newbold and Scott, 2017).…”
Section: Private Transportation Expenditurementioning
confidence: 43%
“…Several studies have shown that older adults require more help with moving around upon driving cessation (Siren and Haustein, 2015; Isherwood et al ., 2017). With regard to the effect of driving cessation on the use of other forms of transport, such as walking, cycling, driving along as a passenger and public transport, the evidence is mixed: both increased use of these other forms (Siren and Haustein, 2015) as well as no increased use (King and Scott-Parker, 2017) have been reported. Furthermore, planning for driving cessation, as well as gradually reducing car use, may contribute to a higher quality of life after cessation (Musselwhite, 2011; Musselwhite and Shergold, 2013).…”
Section: State Of the Art And Scientific Challengesmentioning
confidence: 99%